Saflufenacil efficacy on horseweed and its interaction with glyphosate. Issue 4 (8th November 2013) - Eubank, Thomas W.; Nandula, Vijay K.; Reddy, Krishna N.; Poston, Daniel H.; Shaw, David R.
<x xml:space="preserve">Abstract</x> Saflufenacil is a new herbicide on the market and its effectiveness on horseweed, several populations of which have evolved resistance to glyphosate, is not clear. In this research, the effect of adjuvants on the control of horseweed with saflufenacil in the field, the effect of the interaction between glyphosate and saflufenacil on glyphosate‐resistant and glyphosate‐susceptible horseweed and the patterns of uptake and translocation of glyphosate applied alone and in combination with saflufenacil in horseweed were evaluated. The addition of methylated seed oil to saflufenacil provided the best control of horseweed, with crop oil concentrate being intermediate in effect and non‐ionic surfactant ranking as the least‐effective adjuvant. The interaction between glyphosate and saflufenacil was additive with regards to the control of glyposate‐resistant horseweed. The glyphosate‐susceptible horseweed population absorbed 6–13% more 14C‐glyphosate than the glyphosate‐resistant population. The addition of saflufenacil reduced 14C‐glyphosate translocation in both the glyphosate‐resistant and the glyphosate‐susceptible horseweed populations by at least 6%; however, due to the exceptional efficacy of saflufenacil, these reductions did not reduce the level of control. Saflufenacil holds great potential as an alternative control option for glyphosate‐resistant horseweed and is a valuable tool in the management of resistant weeds.